Behavior of Semi-Rigid Steel Connection for G+3 Symmetrical Structures under Consideration of Seismic Forces Civil Engineering Department: Analysis and Design of Semi-Rigid Steel Connections for G+3 Symmetrical Structures under Seismic Forces (Journal of Advances and Scholarly Researches in Allied Education, 2018)
As the Pinned Rigid connections does not provide true behavior of the structure so the connection called Semi-rigid connection are introduced in the structure by mean of joint spring stiffness to achieve the approximately real behavior of structure. In this paper analysis and design of top seat angle connection is presented and beam-column behavior for maximum deflection joint displacement are compared with different load combination.The results are taken from Staad-pro v8i and designed values are used to calculate relative spring stiffness of beam-column joint and applied on structure to get the semi-rigid type of connection and results are discussed for all three types of connections called pinned, rigid semi-rigid connection.